Multimodal intervention on perception and quality of life of geriatric clients regarding health promotional outcomes at a selected hospitals, Kolar, Karnataka, India - R Vani; Zeanath C. Joseph; Priya R. Aranha (Journal of Family Medicine and Primary Care)
Background of Study: Old age is a privilege for a second childhood and a new stage of opportunity and strength. Older adults are the most rapidly growing segment of the population. By 2050, 80% of all older people will live in low- and middle-income countries. Purpose: To evaluate the effectiveness of multimodal intervention on perception and quality of life among geriatric clients. Methods: Quantitative approach quasi-experimental interventional controlled study with pre-test, post-test design and follow-up for two months, adopted by using purposive sampling technique among 120 geriatric clients who gave consent for participation in the study at two different settings of hospitals from July 2022 to January 2023, Kolar. After obtaining Central Ethics Committee approval, data was obtained using the structured perception questionnaire and WHO Quality of Life questionnaire, and the Multimodal Intervention package consisting of a snake and ladder health promotion strategies game, educational video, and informational pamphlet distributed to the experimental group, whereas routine care was given to the control group followed by post-test group on the 30th and 60th day. Reinforcement was carried out by the investigator on a fortnightly basis reminders through messages. Data were analyzed by using descriptive and inferential statistics such as repeated measures of ANOVA, independent ‘t’- test, paired ‘t-test, and Chi-square. Results: A perception significant effect was demonstrated in the experimental group with enhanced mean, standard deviation from pre-test to post-test I and Post-test II found to be 35.1 ± 7.9, 46.3 ± 6.1, and 48.3 ± 4.7, respectively, without significant changes in the control group. Concerning quality of life, important variations were demonstrated in the experimental group with enhanced mean, SD from pre-test to post-test I and Post-test II found to be 54.76 ± 10.39, 74.15 ± 6.75 and 77.71 ± 4.99, respectively, without any significant changes in the control group. Conclusion: Geriatric population was the biggest beneficiary, multimodal intervention was proven to be effective and can be implemented in hospitals and community settings in improving the perception and quality of life of senior clients to foster healthy aging. CTRI Trial Reg no: CTRI/2021/07/034632.